Risk Factors for Mortality Among COVID-19 Patients in Asia: A Literature Review - Nisa, Hoirun; Utami, Adi Setya Frida; Oktaviani, Anissa Dwi (Poltekkes Kemenkes Jakarta III, 2022)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. This virus was first discovered in Wuhan, China, in December 2019, and was declared an international public health emergency by WHO on January 30, 2020. The Asian region, especially Southeast Asia, is the second-ranked region with the highest deaths of COVID-19 patients. This study aimed to determine risk factors for mortality among COVID-19 patients in the Asian region. This study was a literature review. The articles were searched using the keywords